Cultural Commonality and Specificity in Japanese and Euro-Canadian Undergraduate Students' Leisure Experiences: An Exploratory Study on Control and Positive Affect. (26th May 2016) - Ito, Eiji; Walker, Gordon J.
ABSTRACT: Accumulated cross-cultural research indicates that North Americans typically emphasize primary control (e.g., changing the environment) and high-arousal positive affect (e.g., enthusiasm), whereas East Asians typically emphasize secondary control (e.g., adjusting oneself, accepting the environment) and low-arousal positive affect (e.g., calmness). Therefore, the purpose of this exploratory experience sampling method study was to examine cultural similarities and differences in Japanese ( n = 41) and Euro-Canadian ( n = 15) undergraduate students' control and positive affect as leisure experience. Results indicated that during leisure versus non-leisure participation, (a) both Japanese and Euro-Canadians experienced primary control and high-arousal positive affect more and secondary control (acceptance) less, and (b) Japanese alone experienced secondary control (adjustment) and low-arousal positive affect more. This cross-cultural study contributes to the leisure studies field, both theoretically and practically, by identifying cultural commonality and specificity in leisure experiences as well as leisure's potential role in enhancing psychological well-being.